APPLICATION OF ESSENTIAL OILS AS A PRESERVATIVE TO IMPROVE THE SHELF LIFE OF NILE TILAPIA (Oreochoromisniloticus) - ALBARRACÍN H., William; ALFONSO A., Christian; SÁNCHEZ B., Iván C. (Vitae, 2012)
Some essential oils extracted from herbs and spices have antioxidant activity, it can be used to increase the shelf-life of fillets and cuts of different post-mortem meat. The aim of this work was to study the effect of the antioxidant activity of Thyme and rosemary essential oils on Nile tilapia fillets preservation. The effect of essential oils in tilapia shelf-life was evaluated through the determination of the oxidation products by TBARS analysis and their comparison to some samples without essential oil application. The obtained results show that the use of the two essential oils reduces, between 53 and 96.5%, the oxidative processes of tilapia fillets from the ninth day of storage.